PERLINDUNGAN KONSUMEN TERHADAP PEMBELI SOLAR DI PASAR GELAP STUDI KASUS DI DESA NANGA LIBAU KECAMATAN SEPAUK KABUPATEN SINTANG - NIM. A1012211032, DAVIN JUNIARTA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract A consumer is any person who uses goods and/or services available in society, whether for their own interests, family, other people or other living things and not for trading. Every consumer has legal certainty for themselves to be given protection, as stated in Article 1 number 1 of Law Number 8 of 1999 concerning Consumer Protection which reads,